2016
DOI: 10.15403/jgld.2014.1121.252.chc
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disturbance in Patients with Chronic Hepatitis C Infection: A Systematic Review and Meta-analysis

Abstract: Background & Aims: The involvement of thyroid autoimmunity and dysfunction in patients with chronichepatitis C virus (HCV) infection before interferon-α (IFN-α) therapy remains controversial. We performedthis meta-analysis to evaluate the association of HCV infection with the presence of anti-thyroid antibodiesand dysthyroidism. Methods: A literature search was carried out to collect articles dated up to August 2015 to identify observationalstudies which compared the prevalence of anti-thyroid antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…This result is in accordance with other studies in which higher incidence of hypothyroidism as compared to hyperthyroidism is reported in HCV patients [15, 17]. According to a recent meta-analysis HCV patients are three times more prone to hypothyroidism as compared to control subjects [21]. Keeping in view a high incidence of TPO-Ab in local HCV patients it is expected that this hypothyroidism is probably autoimmune in origin [22].…”
Section: Discussionsupporting
confidence: 91%
“…This result is in accordance with other studies in which higher incidence of hypothyroidism as compared to hyperthyroidism is reported in HCV patients [15, 17]. According to a recent meta-analysis HCV patients are three times more prone to hypothyroidism as compared to control subjects [21]. Keeping in view a high incidence of TPO-Ab in local HCV patients it is expected that this hypothyroidism is probably autoimmune in origin [22].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it was reported that patients who recovered from SARS showed low serum T3 and T4 levels which were due to damage caused by the SARS coronavirus to follicular cells of the thyroid gland [ 137 ]. Viral disease caused by hepatitis C virus (HCV) is also associated with rise in incidence and prevalence of thyroiditis [ 138 ]. A recent report suggests the prevalence of thyroid dysfunction in HIV infected adults [ 139 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…Immunological reactions as well as virus invasion and replication in the affected extrahepatic tissues and organs are the main extrahepatic manifestations of HCV infection [6]. Previous studies have demonstrated that there is a high risk for thyroid autoimmunity and thyroid dysfunction (TD) in patients with HCV infection [7, 8].…”
Section: Introductionmentioning
confidence: 99%